2015
DOI: 10.1007/s00167-015-3774-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined SLAP repair and biceps tenodesis for superior labral anterior–posterior tears

Abstract: Treatment, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 24 publications
0
60
1
Order By: Relevance
“…Recently, several authors have confirmed the findings of Boileau et al. 9 in the first of the few reports that directly compared tenodesis with SLAP repair, suggesting tenodesis as an alternative to SLAP repair, 11 , 12 with evidence of a shorter postoperative recovery, a more predictable outcome, and a higher rate of satisfaction and return to activity with a biceps tenodesis when compared with a repair. 1 , 13 …”
Section: Discussionmentioning
confidence: 70%
“…Recently, several authors have confirmed the findings of Boileau et al. 9 in the first of the few reports that directly compared tenodesis with SLAP repair, suggesting tenodesis as an alternative to SLAP repair, 11 , 12 with evidence of a shorter postoperative recovery, a more predictable outcome, and a higher rate of satisfaction and return to activity with a biceps tenodesis when compared with a repair. 1 , 13 …”
Section: Discussionmentioning
confidence: 70%
“…Injuries to this complex typically occur as a result of repetitive microtrauma through overuse, although acute injuries are possible [12]. Many throwers present complaining of a decrease in velocity and often note pain and mechanical symptoms such as clicking and popping during the late cocking phase of the throwing motion, while tennis or volleyball players may complain of pain during the cocking phase of the serve [18][19][20][21]. Concomitant injuries can occur with relative frequency, such as rotator cuff pathology and instability [22].…”
Section: Diagnosis Presentation and Historymentioning
confidence: 99%
“…An additional study by Gottschalk et al demonstrated a significant improvement in ASES and VAS in 33 patients (average > 46 years old) with type II and IV SLAP tears treated with subpectoral biceps tenodesis and debridement of the superior labrum [67]. A combination of SLAP repair and biceps tenodesis in patients with biceps and superior labral pathology, as presented by Chalmers et al, demonstrated worse outcomes in ASES scores and VAS scores when compared to those that underwent isolated biceps tenodesis or SLAP repair [19].…”
Section: Outcomes Of Biceps Tenodesismentioning
confidence: 99%
“…There has been a recent trend towards biceps tenodesis for the surgical management of type II tears [ 8 , 9 ] and treatment of failed SLAP repairs [ 10 - 12 ]. Few surgeons have performed combined biceps tenodesis and SLAP repair to treat biceps pathology and optimize glenohumeral biomechanics [ 13 ]. However, a recent study showed that this combined procedure results in significantly worse forward flexion and pain scores compared to isolated SLAP repair or isolated biceps tenodesis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few surgeons have performed combined biceps tenodesis and SLAP repair to treat biceps pathology and optimize glenohumeral biomechanics [ 13 ]. However, a recent study showed that this combined procedure results in significantly worse forward flexion and pain scores compared to isolated SLAP repair or isolated biceps tenodesis [ 13 ]. We present a patient who had persistent pain, stiffness, and dysfunction after receiving concomitant biceps tenodesis and superior labral repair.…”
Section: Introductionmentioning
confidence: 99%